Menanamkan Sikap Mencintai Budaya Lokal di Era Globalisasi Pada Anak SMA - Novrianti, Fenni; Rahman, Gusri Andi; Yetti, Yetti (Yayasan Sembilan Pemuda Indonesia, 2023)
In the era of globalization, the personalities of high school children are influenced by globalization. This can be shown by the decline in character values in each individual. For example, lack of manners, cheating on exams, lack of social sensitivity and so on. The method used for this article is descriptive qualitative and literature study. A literature study method was also carried out, namely by collecting data by reading and reviewing literature that had been found by other researchers related to topics and problems related to cultivating an attitude of loving local culture in the era of globalization in high school children. The public's awareness of wanting to maintain their culture is still relatively minimal. Because children nowadays are more interested in foreign culture that has entered their territory, because the foreign culture that has entered is more practical and in line with current development trends.